Prevalence, antibiotic susceptibility and genetic diversity of Campylobacter jejuni isolated from retail food in China. (May 2021) - Wang, Juan; Wang, Zhi; Zhang, Jumei; Ding, Yu; Ma, Zonghao; Jiang, Fufeng; Nie, Xiang; Tang, Shengjun; Chen, Moutong; Wu, Shi; Zeng, Haiyan; Lei, Tao; et al.
Abstract: Campylobacter jejuni is a common and important zoonotic pathogen that can cause bacterial gastroenteritis and other diseases, even leading to Guillain-Barré Syndrome or death. It is therefore necessary to investigate the prevalence and pathogenic risk of C. jejuni . Here, we investigated the prevalence of C. jejuni isolated from retail food in China from 2015 to 2016 and analyzed the distribution of virulence genes, antibiotic susceptibility, and genetic diversity of different isolates. Eighteen out of 1588 samples, collected from 15 main cities of China, were contaminated by C. jejuni, with more than 70% of the strains possessing 14 virulence-genes. Antimicrobial susceptibility testing suggested that all strains were resistant to vancomycin (100%) and cefoperazone (100%), and highly resistant to quinolones (>96%). In contrast, they showed sensitivity to erythromycin. Nevertheless, all the isolated strains were multi-drug resistant. Regarding genetic polymorphism, 20 sequence types (STs) were found by multilocus sequence typing (MLST), ten of which were new STs. Moreover, 40% of the strains could form biofilms, of which 23.33% strains were strong biofilm-forming. In conclusion, our study provides the prevalence and characteristics of C. jejuni isolated from retail food in China, revealing the potential pathogenic risk of C. jejuni in contaminated food. Highlights: A total of 1588 samples were collected and investigated. One positive sample was detected in tomato, which can be consumed directed. 83.33% (25/30) of the isolated strains were resistant to 6 kinds of antibiotics. Twenty STs were found in 30 strains，and 10 of which were new STs. Two strains harbored the GBS related gene wlaN .